Effect of in vitro‐simulated gastrointestinal digestion on the stability and antioxidant activity of blueberry polyphenols and their cellular antioxidant activity towards HepG2 cells. (24th October 2017) - Jiao, Xinyao; Li, Bin; Zhang, Qi; Gao, Ningxuan; Zhang, Xiuyan; Meng, Xianjun
Summary: In this study we investigated the influence of in vitro ‐simulated gastrointestinal digestion on the bioaccessibility and antioxidant activity of polyphenols from blueberries ( Vaccinium spp.). Total phenolic, anthocyanin, and flavonoid content was determined, and extract and digesta compositions were analysed by HPLC‐ESI‐MS/MS. The phenolic compounds were relatively stable under a gastric environment, whereas polyphenols and anthocyanins were unstable under an intestinal environment. The bioaccessibility of polyphenol, anthocyanin, and flavonoid was greatly decreased after the intestinal digestion, and the recoveries were only 13.93%, 1.95%, and 15.68% (the IN sample), respectively. Polyphenolic profile alteration occurred during in vitro ‐simulated gastrointestinal digestion. Changes of phenolic compound antioxidant activity during digestion correlated with polyphenol, flavonoid, and caffeic acid concentrations. Digested extract cellular antioxidant activity was lower than non‐digested extract activity ( P < 0.05). Polyphenol dose–response correlations with cellular antioxidant activity were observed. These results indicated that in vitro ‐simulated gastrointestinal digestion significantly impact polyphenols and their antioxidant activity. Abstract : Effect of in vitro ‐simulated gastrointestinal digestion on the stability and antioxidant activity of blueberry polyphenols and their cellular antioxidant activity towards HepG2 cells.